Analisis Satisfaction Pengguna Publik Transport Bus Trans Siginjai Jambi - Amsori M Das; Ari Setiawan; Pahrur Rozi (Universitas Batanghari Jambi, 2022)
Customer satisfaction is determined by the quality of services and services desired, so that quality becomes a top priority for transportation providers. In Jambi City, the mass transportation that has now been implemented is the Trans Siginjai Bus. Trans Siginjai buses are operated to reduce the use of private vehicles. So that the operation of the Trans Siginjai Bus is required to be able to provide quality service. In order to anticipate user dissatisfaction regarding the services and facilities of the Trans Siginjai Bus, an analysis is needed to determine user satisfaction about the services and facilities provided by the Trans Siginjai Bus. The data obtained is then processed using the Importance Performance Analysis (IPA) method. The data obtained is then processed using the Importance Performance Analysis (IPA) method. The results can be concluded that users will be satisfied with the performance and service of the Trans Siginjai Bus if the manager improves the performance of several factors such as the physical condition of the placement of the Trans Siginjai bus stop, arrivals and departures must be on time, and the service and friendliness of the driver and management of the Trans Siginjai Bus must be improved.